Towards Sharing Rules Between OWL/SWRL and UML/OCL - Milanović, Milan; Gašević, Dragan; Giurca, Adrian; Wagner, Gerd; Devedžić, Vladan (Electronic Communications of the EASST, 2007)
The paper presents a metamodel-driven model transformation approach to interchanging rules between the Semantic Web Rule Language along with the Web Ontology Language (OWL/SWRL) and Object Constraint Language (OCL) along with UML (UML/OCL). The solution is based on the REWERSE Rule Markup Language (R2ML), a MOF-defined general rule language, as a pivotal metamodel and the bidirectional transformations between OWL/SWRL and R2ML and between UML/OCL and R2ML. Besides describing mapping rules between three rule languages, the paper proposes the implementation by using ATLAS Transformation language (ATL) and describes the whole transformation process involving several MOF-based metamodels, XML schemas, EBNF grammars.